Henry Jefferson Leovy, The Laws and General Ordinances of the City of New Orleans 242 (1857) - (:unkn) unknown (My University, 1857)
680: Every keeper of a pistol gallery, the whole tax being levied on each and every gallery, sixty dollars.
Keywords: SHOOTING RANGES OR GALLERIES